واقع تطبيق استراتيجيات الإدارة المرئية في الجامعات الحكومية بمنطقة الرياض في ضوء رؤية المملكة لعام 2030 - القحطاني، ريم بنت ثابت محمد بني زيد (جامعة طنطا - كلية التربية, 2020)
هدفت الدراسة إلى التعرف على درجة تطبيق استراتيجيات الإدارة المرئية ومعوقات تطبيقها في الجامعات الحكومية بمنطقة الرياض في ضوء رؤية المملكة لعام ٢٠٣٠، بالإضافة إلى التعرف على الفروق ذات الدلالة الإحصائية حول تطبيق استراتيجيات الإدارة المرئية ومعوقات تطبيقها لدى رؤساء الأقسام والتي تعود إلى متغيرات (الجنس، المؤهل الأكاديمي، سنوات الخدمة). اتبعت الباحثة المنهج الوصفي. تكون مجتمع الدراسة من جميع مدراء الأقسام في الجامعات الحكومية بمدينة الرياض وتحديدا جامعة الملك سعود، وجامعة الأميرة نوره بنت عبد الرحمن، والجامعة السعودية الالكترونية. اعتمدت الدراسة على طريقة العينة العشوائية من مدراء الأقسام في الجامعات البسيطة، وتم أخذ عينة عشوائية بحجم (١٥٠) الحكومية بمدينة الرياض وتحديدا جامعة الملك سعود، وجامعة الأميرة نوره بنت عبد الرحمن، والجامعة السعودية الالكترونية، تم استرداد (١٣٧) استبانة صالحة للتحليل. في ضوء أهداف الدراسة وأسئلتها فإن الأداة المناسبة لتحقيق أهداف الدراسة هي الاستبانة والتي تكونت من محورين وهما درجة تطبيق استراتيجيات الإدارة المرئية ويتضمن ثلاثة محاور فرعية (وضع قواعد التشغيل، التطهير، القضاء على الهدر)، والمحور الثاني: معوقات تطبيق استراتيجيات الإدارة المرئية. وقد خرجت الدراسة بجملة من النتائج أهمها: بلغت الدرجة الكلية لتطبيق استراتيجية قواعد العمل 74.8%، بلغت الدرجة الكلية لتطبيق استراتيجية التطهير 72.1%، بلغت الدرجة الكلية لتطبيق استراتيجية القضاء على الهدر 70%، بلغت الدرجة الكلية لمعوقات تطبيق استراتيجيات الإدارة المرئية 68.6%، وأشارت إلى وجود فروق ذات دلالة إحصائية بين استجابات أفراد العينة حول تطبيق استراتيجيات الإدارة المرئية لدى رؤساء الأقسام في (جامعة الملك سعود، وجامعة الأميرة نورة، والجامعة السعودية الالكترونية) بمنطقة الرياض في ضوء رؤية المملكة لعام ٢٠٣٠ تعزى لمتغير (الجنس، المؤهل العلمي، سنوات الخبرة).
The study aimed to identify the degree of applying the visual management strategies and the obstacles to their application in the public universities in Riyadh in light of the Kingdom’s vision of 2030. In addition, identify the differences of statistical significance on the implementation of the visual management strategies and the application obstacles for the heads of departments, which are due to several variables (Age, gender, and years of service). The researcher followed the descriptive approach; where the study’s population consisted of department heads in the public universities in Riyadh city, which includes (King Saud University, Princess Norah Bint Abdul Rahman University, and Saudi Electronic University). The study selected the sample based on the random sampling method; as a random sample of (150) department managers was taken at the public universities in Riyadh, specifically King Saud University, Princess Norah Bint Abdul Rahman University, and the Saudi Electronic University; where (137) questionnaires were retrieved for analysis. In light of the objectives and questions of the study, the appropriate tool to achieve the objectives is the questionnaire, which consists of two axes. The first is the application degree of the visual management strategies, which includes three sub-axes (rules of operation, disinfection, elimination of waste). The second is the obstacles to the application of visual management strategies. The reached several conclusions, the most important of which was that the total degree of implementation of business rules strategy reached 74.8%, the overall degree of implementation of the clearance strategy was 72.1%, the total degree of implementation of the waste elimination strategy was 70%, the total degree of obstacles to the implementation of visual management strategies was 68.6%. There were statistically significant differences between the respondents' responses to the implementation of the visual management strategies in the heads of departments at King Saud University, Princess Noura University and Saudi Electronic University in Riyadh in light of the Kingdom’s vision of 2030 due to gender, age, qualification, and years of experience.
Keywords: الجامعات -- الإدارة الجامعية -- الإدارة المرئية -- رؤية 2030 -- الجامعات الحكومية -- الجامعات السعودية -- منطقة الرياض